Gender inequalities in the City of London advertising industry - Wang, Annie; Crewe, Louise (SAGE Publications, 2017)
This paper explores gender relations in the City of London advertising industry. It argues that the gender imbalance in the highest ranking positions and the stifled career progression of women in the industry are a result of social, structural and institutional factors rather than individual choice, lack of ‘talent’ or the absence of mentors or appropriate role models. We discuss the organization and spatiality of the advertising industry in London, the significance of social networking within and beyond the firm, and problematise the notion that female childbearing and caring are the primary determinants of women’s truncated career trajectories in advertising. The research reveals that whilst age, gender and domestic divisions of labour combine to reinforce occupational sexual divisions of labour in the advertising industry in London, these inequality regimes (Acker 2006) are amplified by the industry’s precariousness, informality and requirements for flexibility. Attempting to explain away gendered divisions of labour solely on the basis of women’s role in social reproduction deflects attention away from other key determinants of inequality, most notably the pace of advertising work and the geographical concentration of the industry within London. These are further accentuated by deep-rooted forms of homophily and homosociality – those unspeakable inequalities that call into question the dominant post- feminist rhetoric that ‘all the battles have been won’ (Gill, 2008). We analyse the ways in which homosociality has been crucial in maintaining insidious sexism which has made it very difficult for female creatives to obtain the most prestigious roles at work. Taken together, the organisation and geography of the sector, the rhetoric of buzz and egalitarianism, the ‘motherhood myth’ and the homophilic practices at work within advertising combine to create deep and enduring gendered inequalities.